The Pemanfaatan pekarangan rumah dengan budidaya sayuran dengan metode vertikultur sebagai penyedia gizi masyarakat: metode sistem tanam vertikultur - Linggarweni, Baiq Inggar; Mappanganro, Nurlailah; Nirmawati; Novida, Sari; Putri, Azelia Hidayati; M. Syahroni; Wahyudi, Pahmi (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
the problem faced by housewives in Jempong Barat Village is that they are still lacking understand about how to use narrow yards to be used as land for farming planting vegetables whose nutritional value is very good for the growth of children and toddlers. most of the house yards in Jempong Barat Vilage are still empty and some are only planted with flowers. even though with planting vegetables in the yard can also reduce house hold expenses and can also consume healthy organic vegetables. problems faced by house wives around the Jempong Barat area is the basis for our service team to provide solutions to problems faced by house wives. the solution we offer is to provide counseling and training to house wives in the Jempong Barat region on how to grow vegetables with a vertical cropping system. the output target produced by this PKM is an accredited devitional journal.